Removal of PB (II) using sugar-cane bagasse pith as biosorbent - Trujillo-del Bosque, Alain; Dopico-Ramírez, Daisy; León-Fernández, Vivian; Díaz-López, Cristina (Revista Cubana de Química, 2021)
The search of new treatments and technologies for the removal of toxic metals from wastewater has directed attention towards biosorption in the last years. In the present work the results of the first time use of the sugarcane bagasse pith as biosorbent in the removal of lead from aqueous solutions are shown. The physico-chemical and morphological characterization of the bagasse pith and the optimisation of the experimental conditions for the biosorption were performed. The maximum capacity obtained was 22,39 mg/g. The kinetic data were adjusted to the pseudo second order model and the isotherms for equilibrium studies fitted better to Langmuir´s model. The results indicate that the bagasse pith is an effective adsorbent for the removal of Pb (II) ions present in aqueous solution, so it could be useful for the treatment of industrial wastes containing this metal.